2018
DOI: 10.1152/ajpendo.00142.2017
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular triglyceride synthesis: importance in muscle lipid partitioning in humans

Abstract: Intramuscular triglyceride (IMTG) concentration is elevated in insulin-resistant individuals and was once thought to promote insulin resistance. However, endurance-trained athletes have equivalent concentration of IMTG compared with individuals with type 2 diabetes, and have very low risk of diabetes, termed the "athlete's paradox." We now know that IMTG synthesis is positively related to insulin sensitivity, but the exact mechanisms for this are unclear. To understand the relationship between IMTG synthesis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 61 publications
6
65
2
Order By: Relevance
“…We found that the athletes’ IMCL was significantly lower (soleus) or similar (tibialis anterior) to controls. Although this appears to contradict well-known literature reports of an athlete’s paradox using both biopsy methods (13,28,3234) and 1 H MRS (35,36), this finding is in agreement with literature that reports no such paradox compared to old or young controls (37), obese individuals (38), or in certain fibre types (14). It is known that athletes can have a large depletion-repletion range of IMCL and it is possible that IMCL had not fully recovered since the last training session (24 – 48 hrs prior) as IMCL can still rise significantly after these intervals (39).…”
Section: Discussionsupporting
confidence: 57%
“…We found that the athletes’ IMCL was significantly lower (soleus) or similar (tibialis anterior) to controls. Although this appears to contradict well-known literature reports of an athlete’s paradox using both biopsy methods (13,28,3234) and 1 H MRS (35,36), this finding is in agreement with literature that reports no such paradox compared to old or young controls (37), obese individuals (38), or in certain fibre types (14). It is known that athletes can have a large depletion-repletion range of IMCL and it is possible that IMCL had not fully recovered since the last training session (24 – 48 hrs prior) as IMCL can still rise significantly after these intervals (39).…”
Section: Discussionsupporting
confidence: 57%
“…One study directly measured post-exercise IMTG synthesis by labeled palmitate infusion over 2 h following 90 min of moderate-intensity exercise, and found IMTG fractional synthesis rates to be negative in endurance-trained subjects in the fasted state [10]. This suggests that IMTG is not synthesized in early fasted recovery, but rather can contribute as an energy substrate.…”
Section: The Role Of Imtg Metabolism In Skeletal Muscle Fa Oxidationmentioning
confidence: 99%
“…These processes are energy demanding and accompanied by enhanced post-exercise oxygen consumption (EPOC), of which the magnitude is dependent on exercise duration and intensity [1]. Besides EPOC, the relative contribution from fatty acid (FA) oxidation for whole-body energy turnover is increased, demonstrated by a decreased respiratory exchange ratio (RER), for several hours following aerobic exercise in both untrained and endurance-trained individuals [2][3][4][5][6][7][8][9], and notably also in obese and type 2 diabetic subjects [10]. Even with a carbohydrate-rich meal intake in recovery, the contribution of FAs to oxidation is still increased when compared with resting control conditions [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been shown that ceramides contained in the muscle subfraction enriched in the lipid membranes (subsarcolemmal) are more closely associated with insulin sensitivity in humans (Chung et al 2017;Chung et al 2018). This is probably because of the proximity of these lipid intermediates to the cell membranes, thus increasing the probability of causing inhibition of key insulin signalling events (Bergman et al 2012;Bergman et al 2018;Perreault et al 2018). Even more recent work has validated the importance of not only plasma membrane (subsarcolemmal), but also mitochondrial/endoplasmic reticulum, and nuclear enriched subfraction localization of select ceramide and diacylglycerol species, as well as their relationship with insulin sensitivity .…”
Section: Figure 8 Associations Between Ceramide and Insulin Sensitivitymentioning
confidence: 99%